(3GdJPcQI aj eYQaI GdHjWQIs - (3YHGS Hf Ydj Hf OGhO Hf GdeXaQ jhSa GdQShdj GdZSGfj, Gdedc GdCaVd , J (B778 (3g` s
(3ChdgG (B:s
(3CeG HYO , aCfi fXQJ HjGWf GdbdH hJejR GdYbd ajeG GfYe Gddg Hg Ydi YHGOI ef GdfYe s
(3BNQgG (B:s
(3GcKQ eG jYjT Gdajd YfOfG ai Gdjef NeSjf Gh SJjf SfI heGOhfgG hGddg SHMGfg CYde s
(3fSNI NRGFfjIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B262 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B61s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdChd (B- (3U (B44 s
Keywords: (3GdWHs